2018
DOI: 10.2147/ijn.s154046
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-based colorimetric method for the detection of prostate-specific antigen

Abstract: BackgroundProstate-specific antigen (PSA), a serine protease, is a biomarker for preoperative diagnosis and screening of prostate cancer and monitoring of its posttreatment.MethodsIn this work, we reported a colorimetric method for clinical detection of PSA using gold nanoparticles (AuNPs) as the reporters. The method is based on ascorbic acid (AA)-induced in situ formation of AuNPs and Cu2+-catalyzed oxidation of AA. Specifically, HAuCl4 can be reduced into AuNPs by AA; Cu2+ ion can catalyze the oxidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
(50 reference statements)
0
17
1
Order By: Relevance
“…Proteolytic enzymes, which degrade specific proteins, have played an important role in the living system, from the biomolecular to the organ level. , For instance, matrix metalloproteinases (MMPs) degrade both matrix and nonmatrix proteins in the extracellular environment of cells and are involved in the activation/inactivation of several biomolecules by the cleavage of cell surface receptors, the release of apoptotic ligands, and so forth. Some proteolytic enzymes have different expression levels based on the physiological conditions of hosts and organs. Typically, the concentration of the MMPs is relatively high in the case of the cancerous state because they are utilized on the angiogenesis of tumor sites for nutrient and oxygen supply. ,, In this respect, proteolytic enzymes have been widely used as biomarkers for the diagnosis of some specific diseases such as cancers, neurodegenerative diseases, and other biological reactions. To detect proteolytic biomarkers selectively, most of the proteolysis-based biosensors have exploited specific peptide sequences consisting of fewer than 10 amino acids that could be cleaved by particular proteolytic enzymes such as MMPs, the caspase family, and prostate-specific antigens (PSAs). Using specific sequences can be done to measure in a very selective manner, similar to an immunoassay.…”
mentioning
confidence: 99%
“…Proteolytic enzymes, which degrade specific proteins, have played an important role in the living system, from the biomolecular to the organ level. , For instance, matrix metalloproteinases (MMPs) degrade both matrix and nonmatrix proteins in the extracellular environment of cells and are involved in the activation/inactivation of several biomolecules by the cleavage of cell surface receptors, the release of apoptotic ligands, and so forth. Some proteolytic enzymes have different expression levels based on the physiological conditions of hosts and organs. Typically, the concentration of the MMPs is relatively high in the case of the cancerous state because they are utilized on the angiogenesis of tumor sites for nutrient and oxygen supply. ,, In this respect, proteolytic enzymes have been widely used as biomarkers for the diagnosis of some specific diseases such as cancers, neurodegenerative diseases, and other biological reactions. To detect proteolytic biomarkers selectively, most of the proteolysis-based biosensors have exploited specific peptide sequences consisting of fewer than 10 amino acids that could be cleaved by particular proteolytic enzymes such as MMPs, the caspase family, and prostate-specific antigens (PSAs). Using specific sequences can be done to measure in a very selective manner, similar to an immunoassay.…”
mentioning
confidence: 99%
“…(a) Colorimetric assay for detection of PSA based on in situ synthesis of gold nanoparticles from the precursor HAuCl 4 catalysed by ascorbic acid in absence of Cu(II). 223 The design used peptide-modified magnetic nanoparticles containing a Cu 2+ binding triad. The peptide was cleaved by PSA and the Cu 2+ binding triad released.…”
Section: Colorimetricmentioning
confidence: 99%
“…A colorimetric method for prostate-specific antigen (PSA) detection was developed by Liu 223 using the formation or inhibition of formation of AuNPs as a colorimetric indicator. The method was based on ascorbic acid induced formation of AuNPs, a process that can be inhibited by the presence of Cu 2+ .…”
Section: Bench-top or In Vitro Applicationsmentioning
confidence: 99%
“…These limitations stimulate the emergence of various artificial enzyme mimics, such as nanozymes, which are defined as nanomaterials with enzyme-like characteristics . Since the first discovery of peroxidase-mimic activities in magnetic Fe 3 O 4 nanoparticles (NPs), numbers of nanomaterials based on vanadium oxides, , noble metals (Au, Ag, Pt, and Pd), copper oxides, carbon, and manganous have been reported as antioxidant enzyme mimics. In addition, novel single-atom nanozymes such as the Fe-N-C electrocatalyst have been also discovered with exceptional per­(oxidase)-like activity and widely explored as alternatives to natural enzymes. , Developing nanozymes with biocatalytic properties in a biological context is intriguing to peruse more advanced functions of natural enzymes, such as cost-effectiveness, mass production, stability, and better tolerance toward harsh environments. , Lin et al first reported a copper tannic acid coordination for ROS scavenging in cigarette smoke, opening up an opportunity for the modification of cigarette filters by nanozymes.…”
Section: Introductionmentioning
confidence: 99%